New Prespective of Brand Personality in Indonesia - Gabriela Ditta Aurelya Rafa; Teofilus Teofilus; Auditia Setiobudi (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
The footwear industry is one of the industry sectors that has a prospective influence on the growth of the Indonesian economy. The need for footwear is now transforming into a part of a lifestyle. The aim of this research is to look at and analyze what brand personality factors are appropriate in the context of developing countries, especially Indonesia, based on literary studies by Aaker (1997), Geuens (2009), and Davies. (2018). This research provides a new insight into brand personality in the context of Indonesia's perspective. The sample is a local shoe user with a set sample quota in the five provinces that have the most shoe companies registered with the Ministry of Industry. The study used a total of 225 respondents. The results show that the brand's personality dimension has formed. The study provides a new perspective on the brand personality dimension from an Indonesian perspective, given that no study specifically defines brand personality. This research has become interesting because there are still very few articles describing the concept of brand personality in developing countries, which limits researchers' preparation of research. In the future, it is expected that business owners will begin to consider the importance of the essence of a brand so that brand personality is created for local brands in Indonesia.